Gully evolution and numerical simulation using the SIMWE model in Brazil - Hartwig, Marcos Eduardo; Inacio Alves, João Pedro [UNESP] (Elsevier, 2025)
Gullies epitomize the pinnacle of hillslope erosion, causing significant economic and environmental losses worldwide. Within the municipality of Alegre, located in the State of Espírito Santo, southeastern Brazil, approximately a hundred gullies have been identified. This study endeavors to delineate the spatio-temporal evolution of two such gullies, alongside evaluating the efficiency of the SIMulation of Water Erosion (SIMWE) model. The methodology integrates aerial photogrammetric surveys, multitemporal image analysis, hillslope morphology assessment, geological and pedological analysis, geotechnical soil testing, and numerical modeling. Two scenarios were considered for the numerical simulation: one representing a single extreme rainfall event and the other accounting for a series of rainfall events from 2007 to 2021. The study reveals that sizable gullies, measuring thousands of cubic meters and carved in steep slopes, can undergo rapid expansion within just over a decade. The origin of these gullies is linked to terracette failures caused by intensive cattle farming practices. Their evolution is influenced by multiple interacting factors, including landslides, soil cracks, and variations in soil horizon erodibility. Furthermore, the SIMWE algorithm aids in understanding surface runoff dynamics, pinpointing the highest erosion rates in tandem with the emergence of gullies. The SIMWE model is a valuable tool for identifying areas prone to hillslope erosion. However, it was unable to accurately replicate long-term gullying.
Keywords: Gully incision; Hillslope erosion; Land degradation; Numerical modeling; Pasture